2012
DOI: 10.1021/bi3011362
|View full text |Cite
|
Sign up to set email alerts
|

Farnesyl Diphosphate Analogues with Aryl Moieties Are Efficient Alternate Substrates for Protein Farnesyltransferase

Abstract: Farnesylation is an important post-translational modification essential for proper localization and function of many proteins. Transfer of the farnesyl group from farnesyl diphosphate (FPP) to proteins is catalyzed by protein farnesyltransferase (FTase). We employed a library of FPP analogues with a range of aryl groups substituting for individual isoprene moieties to examine some of the structural and electronic properties of analogue transfer to peptide catalyzed by FTase. Analysis of steady-state kinetics f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
0
17
0
1
Order By: Relevance
“…Similarly, isoprenoid analogues are being developed to disrupt interactions with prenylated proteins. 57 In those cases, it will be important to know whether such analogues are incorporated into prenylated proteins with a specificity profile similar to farnesyl groups. While in vitro assays with individual peptides do allow the catalytic efficiencies of different isoprenoid substrates to be compared, such experiments do not allow global variations in peptide substrate efficiency to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, isoprenoid analogues are being developed to disrupt interactions with prenylated proteins. 57 In those cases, it will be important to know whether such analogues are incorporated into prenylated proteins with a specificity profile similar to farnesyl groups. While in vitro assays with individual peptides do allow the catalytic efficiencies of different isoprenoid substrates to be compared, such experiments do not allow global variations in peptide substrate efficiency to be studied.…”
Section: Resultsmentioning
confidence: 99%
“…For example, analog 13 , where all isoprene units were replaced with aryl groups, was an efficient FTase substrate. 69 They reported that the anilinogeranyl-based isoprenoid analogs 14 and 15 , which have 2–5 orders of magnitude less hydrophobicity compared with FPP, were substrates for FTase. Proteins modified with these analogs were processed by downstream enzymes Rce1 and Icmt; however, the resulting modified proteins were not biologically active, indicating the importance of increased hydrophobicity upon prenylation.…”
Section: Isoprenoid Analogsmentioning
confidence: 99%
“…, Km = 1.5 µM), (65) kcat values for both dns-GC(x)3X peptides are reduced ~30-fold while Km increases ~4-fold for dns-GCAVGP and decreases ~3-fold for dns-GCMIIM. When compared to dns-GCMII and dns-GCAVG, the potential sequences derived from proteolytic trimming, kcat/Km was increased 25-fold for dns-GCAVG relative to dns-GCVAGP and decreased 2-fold for dns-GCMII relative to dns-GCMIIM.…”
Section: Steady-state Analysis Of Dns-gc(x)3x Peptide Reactivity Withmentioning
confidence: 91%